Management of Acute Myeloid Leukemia in the Intensive Care Setting. (October 2015) - Cowan, Andrew J.; Altemeier, William A.; Johnston, Christine; Gernsheimer, Terry; Becker, Pamela S.
Patients with acute myeloid leukemia (AML) who are newly diagnosed or relapsed and those who are receiving cytotoxic chemotherapy are predisposed to conditions such as sepsis due to bacterial and fungal infections, coagulopathies, hemorrhage, metabolic abnormalities, and respiratory and renal failure. These conditions are common reasons for patients with AML to be managed in the intensive care unit (ICU). For patients with AML in the ICU, providers need to be aware of common problems and how to manage them. Understanding the pathophysiology of complications and the recent advances in risk stratification as well as newer therapy for AML are relevant to the critical care provider.